E-088 Endovascular management of AVM-associated intracranial aneurysms: a systematic literature review. (23rd July 2022) - Kashkoush, A; El-Abtah, M; Petitt, J; Achey, R; Bain, M; Moore, N
Abstract : Objective: Intracranial aneurysms are present in up to 18% of arteriovenous malformations (AVMs) and increase the risk of intracranial hemorrhage. No consensus exists on the optimal treatment strategy for AVM-associated aneurysms. The goal of this study was to systematically review current endovascular treatment methods of AVM-associated intracranial aneurysms, radiographic outcomes, and periprocedural complications. Methods: A systematic review was performed in accordance with PRISMA guidelines to identify studies that investigated the use of endovascular treatments for the management of patients with AVM-associated aneurysms. Collected variables included aneurysm and AVM location, aneurysm size and characteristics (intranidal versus feeding artery), AVM and aneurysm treatment modality, periprocedural complications, and long-term clinical and radiographic outcomes. Results: A total of seven studies with 216 patients and 287 AVM-associated intracranial aneurysms were included in the analysis. Two-hundred aneurysms were flow-related (69.7%; 200/287), 80 were intranidal (27.9%; 80/287), and 7 were unrelated (2.4%; 7/287). Complete occlusion was 71% (15/21) for aneurysmal coil embolization and 99% (104/105) for parent vessel sacrifice. Of the 13 aneurysms treated with ethanol sclerotherapy, eight were successfully obliterated (8/13; 61%) using ethanol sclerotherapy alone and the rest required adjunct endovascular embolization for obliteration of the artery and associated aneurysm. Periprocedural complications were reported in 25 patients (25/216; 11.6%) and consisted of ischemic symptoms, intracranial hemorrhage, and coiling complications. Conclusion: Endovascular management options of AVM-associated intracranial aneurysms are limited and mostly comprised of primary aneurysmal coil embolization or parent vessel sacrifice using coils or liquid embolics. Embolization strategy depends on a number of factors such as AVM angioarchitecture, rupture status, and adjunct AVM treatments. Disclosures: A. Kashkoush: None. M. El-Abtah: None. J. Petitt: None. R. Achey: None. M. Bain: 2; C; CERENOVUS, Integra. 6; C; advisory board for Stryker. N. Moore: None.